PENERAPAN METODE TALKING ADVENTURE MAP UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI SISWA KELAS III SD DALAM PEMBELAJARAN BAHASA INDONESIA - Intan Khairasyani; Pratiwi Kartika Sari; Virda Nurlita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the communication skills of third-grade elementary school students in Indonesian language learning through the implementation of the Talking Adventure Map (TAM) method supported by visual media. The research was conducted at SDN Pondok Cabe Ilir 01 using the Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, which consists of a pre-cycle, Cycle I, and Cycle II with the stages of planning, action, observation, and reflection. Data were collected through observation, written tests (pre-test and post-test), documentation, and field notes, and were then analyzed using both quantitative and qualitative methods. The results showed a significant improvement in students' communication skills. In the pre-cycle stage, the average student score was 66.56with a mastery level of 47%. After Cycle I, the average score increased to 68.59 with 66% mastery, and in Cycle II, the average increased to 80.6 with 84% mastery. The implementation of the TAM method effectively increased student engagement, confidence, and communication skills. This method also helped students expand their vocabulary and express ideas more systematically in a fun learning environment. Therefore, the Talking Adventure Map method can be considered an alternative instructional method to enhance elementary school students' oral communication skills.